2023
DOI: 10.3390/metabo13040465
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione for Food and Health Applications with Emphasis on Extraction, Identification, and Quantification Methods: A Review

Abstract: Glutathione is a naturally occurring compound that plays a crucial role in the cellular response to oxidative stress through its ability to quench free radicals, thus mitigating the risk of potential damage, including cell death. While glutathione is endogenously present in different plants and animal cells, their concentration varies considerably. The alteration in glutathione homeostasis can be used as a potential marker for human diseases. In the case of the depletion of endogenous glutathione, exogenous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…The flakes of H10 showed the largest reduction (80.61%), while the lowest reduction (63.61%) of GSH content was noticed in the flakes of H1 after popping, signifying it as an important genotype which retains, at the same time, a greater GSH pool after microwave popping and GSH source. This is an important trait, since it is well known that cereal grains are a low-GSH source in nutrition [ 23 ]. When compared to the kernels, the effect of popping led to an increased TPC content, being the most pronounced in flakes of H1 (4.27%) and the least pronounced in flakes of H12 (1.05%).…”
Section: Resultsmentioning
confidence: 99%
“…The flakes of H10 showed the largest reduction (80.61%), while the lowest reduction (63.61%) of GSH content was noticed in the flakes of H1 after popping, signifying it as an important genotype which retains, at the same time, a greater GSH pool after microwave popping and GSH source. This is an important trait, since it is well known that cereal grains are a low-GSH source in nutrition [ 23 ]. When compared to the kernels, the effect of popping led to an increased TPC content, being the most pronounced in flakes of H1 (4.27%) and the least pronounced in flakes of H12 (1.05%).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some reports have confirmed that ascorbic acid can enhance the immune response and antioxidant capacity of birds, especially under stress conditions (Shewita et al, 2019;Ahmadu et al, 2016;Barrio, et al, 2020). Glutathione is one of the essential natural antioxidants that can be linked to health-promoting effects on birds, humans, and plant life (Al-Temimi, et al, 2023).…”
Section: Ascorbic Acid and Gsh Content Of Free Range Goose Egg Yolk D...mentioning
confidence: 96%
“…70-18-8), and the content of GSH is approximately 90% and that of GSSG is approximately 10% in unstressed cells. 1 Owing to the presence of a thiol group (−SH), GSH possesses reducing properties and metal chelating abilities; hence, it is an important antioxidant in the human body. GSH plays a critical role in various physiological processes, such as the elimination of toxins, maintenance of redox balance, reduction of oxidative stress, and regulation of immune system functions.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the main active substance is GSH (Figure , CAS registry no. 70-18-8), and the content of GSH is approximately 90% and that of GSSG is approximately 10% in unstressed cells . Owing to the presence of a thiol group (–SH), GSH possesses reducing properties and metal chelating abilities; hence, it is an important antioxidant in the human body.…”
Section: Introductionmentioning
confidence: 99%